1999
DOI: 10.1128/jcm.37.8.2548-2552.1999
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiological Study ofHaemophilus influenzaeSerotype b Strains Obtained from Children with Meningitis in Japan

Abstract: We report an epidemiological study of 30 Haemophilus influenzae serotype b (Hib) strains derived from the cerebrospinal fluid of children with meningitis. The Hib strains were biotyped, tested for β-lactamase production, and genotyped by long PCR-ribotyping, random amplified polymorphic DNA (RAPD) analysis, and genomic DNA restriction fragment length polymorphism (RFLP) analysis by pulsed-field gel electrophoresis (PFGE). The phenotypic study characterized 22 of the strains (73%) as biotype I. A genotypic stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Three of these patterns were composed of a single band of 884, 1,265, 650 bp and were designated RAPD patterns A, B, and C, respectively. One was composed of a clear band of 420 bp and three weak bands of 1,265, 918, and 444 bp, and it was designated RAPD pattern D. The RAPD pattern A was produced with DNAs extracted from the type strain of E. rhusiopathiae and from the reference strains of serovars 1a, 1b, 2, 4, 5,6,8,9,11,12,15,16,17,19, and 21 and type N, believed to be E. rhusiopathiae. The RAPD pattern B was produced with DNAs extracted from the type strain of E. tonsillarum and from the reference strains of serovars 3, 7, 10, 14, 20, 22, and 23, considered to be E. tonsillarum.…”
Section: Resultsmentioning
confidence: 99%
“…Three of these patterns were composed of a single band of 884, 1,265, 650 bp and were designated RAPD patterns A, B, and C, respectively. One was composed of a clear band of 420 bp and three weak bands of 1,265, 918, and 444 bp, and it was designated RAPD pattern D. The RAPD pattern A was produced with DNAs extracted from the type strain of E. rhusiopathiae and from the reference strains of serovars 1a, 1b, 2, 4, 5,6,8,9,11,12,15,16,17,19, and 21 and type N, believed to be E. rhusiopathiae. The RAPD pattern B was produced with DNAs extracted from the type strain of E. tonsillarum and from the reference strains of serovars 3, 7, 10, 14, 20, 22, and 23, considered to be E. tonsillarum.…”
Section: Resultsmentioning
confidence: 99%
“…A Japanese study concerning the capsular types of Hi isolates from pediatric patients with respiratory tract infections showed that all encapsulated strains (types b and f) displayed biotype I [8] . Of the 30 Hib isolates from the cerebrospinal fluid of Japanese children with meningitis, 22 (73.3%) were characterized as biotype I [9] . Thus, this biochemical phenotypic assay is useful to assess the prevalent type of Hi based on the data combined with the capsular genotypes.…”
Section: Discussionmentioning
confidence: 99%